Patient Legal Protection in the Digital Era and Study of Telemedicine Services in Indonesia - Dalimunthe, Wirandi; Ismaidar, Ismaidar; Simarmata, Marice (Universitas Muhammadiyah Sumatera Utara, 2025)
The development of digital technology has brought significant transformations in the health sector, including in the implementation of telemedicine. Telemedicine allows interaction between doctors and patients through electronic media, which offers convenience in health services, especially in remote areas. However, the practice of telemedicine also poses various challenges, especially related to legal protection for patients. This study aims to examine the legal protection provided to patients in the digital era, especially in the context of telemedicine in Indonesia. In addition, this study also evaluates the telemedicine regulations that apply in Indonesia. Government Regulation No. 28 of 2024 is an implementing regulation of Law Number 17 of 2023 concerning Health. Regulation of the Minister of Health Number 20 of 2019 regulates the Implementation of Telemedicine Services Between Health Service Facilities. Through a normative juridical approach, this study highlights various legal issues related to patient data privacy, health service standards, legal responsibilities of medical personnel, and guarantees of legal protection for patients in telemedicine services. The results of this research are expected to contribute to the development of more comprehensive regulations and ensure that patients' rights are protected in the digital era